64 Association of 24-hour In-house Neonatologist Coverage with Outcomes of Extremely Preterm Infants. (29th October 2021) - Debay, Anthony; Shah, Prakesh; Lodha, Abhay; Shivananda, Sandesh; Redpath, Stephanie; Seshia, Molly; Dorling, Jon; Lapointe, Anie; Canning, Rody; Strueby, Lannae; Beltempo, Marc
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Medical team composition at the delivery of high-risk neonates may contribute to better outcomes. The presence of 24-hour (h) in-house staff neonatologist (NN) may improve delivery room (DR) care practices and outcomes. Objectives: To assess if 24-h in-house NN coverage is associated with better care practices and outcomes among inborn infants born < 29 weeks GA. Design/Methods: Cross-sectional cohort study of 2476 inborn infants born at 23-28 weeks gestation, admitted in 2014-2015 to Canadian Neonatal Network level 3 NICUs with a maternity unit that participated in a 2015 survey on NICU coverage. Exposures were classified using survey responses based on the most senior provider offering 24-h in-house coverage: NN, fellow, and no NN/fellow. Primary outcome was death and/or major morbidity (bronchopulmonary dysplasia, severe neurological injury, late-onset sepsis, necrotizing enterocolitis, retinopathy of prematurity). Multivariable logistic regression analysis was used to assess the association between exposures and outcomes and adjust for confounders with generalized estimating equations to account for clustering within each site. Results: Among the 28 participating NICUs, most senior providers ensuring 24-h in-house coverage were NN (32%, 9/28), fellows (39%, 11/28), and no NN/fellow (29%, 8/28). Infants' characteristics are shown in Table 1. No NN/fellow coverage and 24-h fellow coverage were associated with higher odds of infants receiving DR chest compressions or epinephrine compared to 24-h NN coverage (adjusted odds ratio [AOR] 4.72, 95% CI 2.12-10.6 and AOR 3.33, 95% CI 1.44-7.70, respectively) (Table 2). 24-h fellow coverage was associated with higher odds of normothermia (36.5°C-37.2°C) on admission (AOR 2.26, 95% CI 1.51-3.37) compared to 24-h NN coverage (Table 2). Rates of mortality or major morbidity did not differ significantly among the three groups: NN, 63% (249/395); fellow, 64% (1092/1700); no NN/fellow, 70% (266/381). Compared to 24-h NN coverage, 24-h fellow coverage was associated with lower odds of mortality (AOR 0.62, 95% CI, 0.43-0.88) (Table 2). Conclusion: 24-h in-house NN coverage was associated with lower rates of DR chest compressions or epinephrine use; however, it was not associated with death and/or major morbidity. These results are from a survey linked cohort, and data on the actual presence of individuals in NICU/resuscitation is unknown. Future prospective research on care providers present in the NICU, and its impact on outcomes, is needed.